Supporting And Inhibiting Factors of The Acceleration of Stunting Reduce and Stunting Prevention Policy in Penajam Paser Utara Regency - Thalita Rifda Khaerani; Muhammad Fazar (Universitas of Muhammadiyah Makassar, 2022)
Stunting is a condition of failure to thrive caused by nutritional problems. Indonesia has set a strategy for accelerating stunting reduction that focuses on several priority areas for the highest stunting cases, including East Kalimantan, which is ranked the 14th highest stunting case. This study aims to determine the supporting and inhibiting factors in the policy to accelerate the decline and prevent stunting prevention in North Penajam Paser Regency. The type of research used is descriptive qualitative with data collection techniques through observation, interviews, documentation and literature studies as well as analytical techniques using interactive models. Based on the results of the study, it was found that the supporting factors were the support from the government and the private sector through the corporate social responsibility (CSR) program, the support for increasing the capacity of human resources, the availability of operational support facilities and infrastructure and the placement of Posyandu officers and cadres in each village/kelurahan was adequate and the inhibiting factors were: lack of coordination between stakeholders causing cross-sectoral egos, inadequate budgets, public perception of stunting which is considered normal because children are in healthy condition, training is only carried out for community cadres, the COVID-19 pandemic has resulted in schools closing and health facilities being limited.